An Artist among the Puritans:Challenging a Cultural Image in Hawthorne’s The Scarlet Letter - Michèle BONNET (E-REA)
This essay about The Scarlet Letter explores from a textual and cultural perspective the place of the artist in New England culture, both that of Puritan seventeenth-century Boston and of the nineteenth-century Salem satirized in « The Custom-House ». It shows how, in his typically ironic style, Hawthorne covertly subverts New England’s critical view of the artist who, rather than being an alleged agent of social disruption, turns out to be the cement of the community, indeed a « necessary » element. The text first painstakingly disproves that storytelling and art in general might run counter to the Puritan work ethic. The artist, either male or female, is no « idler ». It shows in addition that he or she complies with another Puritan imperative that lived on into nineteenth-century New England culture : being serviceable to the community. Paradoxically enough, this, we also discover, is achieved through a quality held in deep suspicion by this same culture, imagination or fancy (the pointedly indifferent use of the terms serving a particular purpose here), which the text rehabilitates as the artist’s exemplary quality, also crediting the latter with a larger than ordinary faculty for sympathy, or love or, in the text’s coded language, « affection ». These are the twin qualities that make the artist, the man of letters in particular, superior to the history writer and better-equipped than him for federating the nation.